Statistical Antenna Proximity Effect Modeling with Uncertainty Impedance Ellipses - Pedro Luis Carro; Jesús de Mingo; Paloma García-Dúcar; Antonio Valdovinos (International Journal of Antennas and Propagation)
User effects on portable antennas can decrease the global terminal performance, such as reducing the battery life or the wireless coverage. People presence will modify the input impedance, the far field radiation pattern, the radiation efficiency, and the near field. In this paper, we investigate the influence of the user on the input impedance by means of a new statistical approach which relies on uncertainty, where a handheld antenna works in two modes (data and talk) while people couple to the antenna. Studying some reflection coefficient measurements performed with a vector network analyzer (VNA), a standard framework based on uncertainty ellipses is developed. Finally, the method is applied to some antenna prototypes, showing its advantages and reliability to quantify and compare proximity effects.